(untitled) (Bangladesh Journal of Zoology, 2026)
Helicobacter pylori is an extensively prevalent gastrointestinal pathogen that continues to pose a noteworthy public health challenge worldwide, predominantly in low and middle-income countries where overcrowding, poor hygiene, and limited access to healthcare persist common. The current study was undertaken to address this knowledge paucity by evaluating the prevalence of H. pylori infection during early pregnancy and reconnoitering its potential health implications among women residing in an urban slum in Dhaka. It was a descriptive, hospital-based cross-sectional study, conducted between August 2017 and April 2018. A total of 45 women, permanent residents of Kamrangir Char in their early trimester (9 to 16 weeks) of pregnancy, were enrolled after securing informed consent from Maternal and Child Health Training Institute (MCHTI), Azimpur. Stool samples were collected from each participant and analyzed for the detection of H. pylori antigen using a clinically authorized enzyme-linked immunosorbent assay (ELISA). Laboratory procedures, data entry, and statistical analyses, were carried out at the Nutrition, Immunology, and Toxicology Laboratory of International Centre for diarrheal disease research, Bangladesh icddr,b in accordance with standardized quality-control protocols. The results revealed a high prevalence of H. pylori infection, with 75.6% of the participants testing positive. Supplementary stratification of the data by maternal age and gestational age did not demonstrate any statistically significant variation in infection prevalence. The socio-demographic profile of the study population reflected widespread poverty, low levels of formal education, and limited dietary diversity factors that collectively increase susceptibility to chronic infections and nutritional deficiencies during pregnancy. Given the pathogen’s potential to impair nutrient absorption and contribute to poor maternal and fetal outcomes, the integration of H. pylori screening, targeted nutritional interventions, and health education into routine antenatal care is strongly recommended for high-risk populations in similar settings. Bangladesh J. Zool. 53(3): 297-309, 2025